Graduate competencies based on the aspect of organizational activity in industry 4.0 - Siti Sahara; Vina Oktaviani; Efri Sandi; Vania Zulfa; Rezi Berliana Yasinta; Rika Sa'diyah; Siti Shofiyah; Ilmi Zajuli Ichsan (International Journal of Evaluation and Research in Education (IJERE), 2024)
Industrial revolution 4.0 has an impact, namely the demand for the labor market has changed, where the automation revolution replaces work that is usually capable of being done by humans and poses the risk of termination of employment. The purpose of this study is to identify the competencies that must be possessed by graduates based on aspects of organizational activity according to the needs of the industry. The data in this study are in the form of literacy studies, data from direct interviews with the industry and questionnaires to a number of respondents. Testing the validity of the questionnaire using the product moment correlation formula, followed by reliability testing using the Cronbach alpha. Meanwhile, to determine the sample size in this study using the purposive sampling technique with a total of 75 respondents consisting of practitioners and graduates of the Faculty of Engineering, Universitas Negeri Jakarta (FT-UNJ), Indonesia. The research method is carried out with a qualitative descriptive method which is intended to obtain results that describe in detail the competencies that must be possessed by graduates based on aspects of organizational activity according to the needs of the industry. The results of the research related to the competence of graduates needed by industry 4.0 based on aspects of organizational activity, namely open minded, decision making abilities, emotional intelligence, cognitive flexibility, service orientation, coordinating with others, leadership skills, critical thinking and creativity skills, skills in technology, and complex problem solving.